Implementasi SCRUM pada Pengembangan Aplikasi Sistem ADI STETSA SMAN 4 Malang: Bidang Bimbingan Konseling - Mahisha Laila; Aji Wibawa; Ilham Zaeni; Zafifatuz Zuhriyah (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
The development of digital applications at State 4 Malang, including counseling, aims to facilitate the management of data related to teachers and students. Counseling provides services for the personal, social, learning, and career problems of students and teachers. The development method used is the SCRUM model framework. The service process in the field of counseling has not yet a clear service flow. Thus, with the SCRUM method, the information system development process can change and there is no need to return to the initial steps of the method. SCRUM can manage projects more efficiently and make teamwork more effective through a step process known as sprint. The process of implementing the sprint in the creation of the Application Digital Studium Et Sapientia (ADI STETSA) project was carried out in 5 sprints. The field of counseling was developed in the 4th sprint. The features developed have been approved by the person in charge of the counseling field. The resulting features are alumni, specialization and cross-interest, and consultation. An information system based on a website and a mobile application. This development is equipped with a software requirement specification document as a reference for using the system, especially for schools. Pengembangan aplikasi digital pada Sekolah Menengah Atas Negeri 4 Malang, termasuk bimbingan konseling, bertujuan untuk memudahkan pengelolaan data yang berkaitan dengan guru, dan siswa. Bimbingan konseling memberikan layanan masalah pribadi, sosial, belajar, dan karier siswa serta guru. Metode pengembangan yang digunakan adalah kerangka kerja model SCRUM. Proses pelayanan bidang bimbingan konseling belum memiliki alur pelayanan yang jelas. Sehingga, dengan metode SCRUM proses pengembangan sistem informasi dapat berubah dan tidak perlu kembali pada langkah awal metode. SCRUM dapat mengelola proyek menjadi lebih efisien dan membuat kerja tim menjadi lebih efektif melalui proses tahapan yang disebut dengan sprint. Proses pelaksanan sprint dalam pembuatan proyek sistem Aplikasi Digital Studium Et Sapientia (ADI STETSA) dilakukan sebanyak 5 sprint. Bidang bimbingan konseling dikembangkan pada sprint ke-4. Fitur yang dikembangkan telah disetujui oleh penanggung jawab bidang bimbingan konseling. Fitur yang dihasilkan yaitu alumni, peminatan dan lintas minat serta konsultasi. Sistem informasi yang dibuat berbasis website dan aplikasi mobile. Pengembangan ini dilengkapi dengan dokumen spesifikasi kebutuhan perangkat lunak sebagai acuan menggunakan sistem khususnya untuk pihak sekolah.